Analysis of Work Posture Using the Muscle Fatigue Assessment (MFA) and Novel Ergonomic Postural Assessment (NERPA) - Dian Palupi Restuputri; Rofiqul Umam Achmad; Muhammad Lukman; Ilyas Masudin (Jurnal Ilmiah Teknik Industri, 2021)
A company needs to know each employee's ability to reduce accidents that happen to workers due to a lack of study on ergonomic principles. The research was conducted at a construction company producing paving blocks in Kediri. The paving production capacity at the company is 1000 paving/day. In 2017, three work accidents were caused by the fast pace of workers reaching the tired phase while working. Pulling, lifting, and putting down in carrying weighty loads and the repetition frequency of intense activities trigger stress on body parts that affect the worker's performance. The purpose of this study is to assess and provide recommendations for improvements in work activities that have a hazardous risk value based on the MFA and NERPA assessment methods. The research on the MFA method shows that activities with dangerous risk (high/very high) were in transportation activities. For the NERPA method, activities with dangerous risks were in 3 activities at the finishing work station with a final score of 7. Recommendations for improvement are work posture improvement, physical environment improvement, and work facilities.